Incidence, Determinants, and Outcomes of Coronary Perforation During Percutaneous Coronary Intervention in the United Kingdom Between 2006 and 2013: An Analysis of 527 121 Cases From the British Cardiovascular Intervention Society Database. (August 2016) - Kinnaird, Tim; Kwok, Chun Shing; Kontopantelis, Evangelos; Ossei-Gerning, Nicholas; Ludman, Peter; deBelder, Mark; Anderson, Richard; Mamas, Mamas A.
Abstract : Background—: As coronary perforation (CP) is a rare but serious complication of percutaneous coronary intervention (PCI) the current evidence base is limited to small series. Using a national PCI database, the incidence, predictors, and outcomes of CP as a complication of PCI were defined. Methods and Results—: Data were prospectively collected and retrospectively analyzed from the British Cardiovascular Intervention Society data set on all PCI procedures performed in England and Wales between 2006 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. In total, 1762 CPs were recorded from 527 121 PCI procedures (incidence of 0.33%). Patients with CP were more often women or older, with a greater burden of comorbidity and underwent more complex PCI procedures. Factors predictive of CP included age per year (odds ratio [OR], 1.03; 95% confidence intervals, 1.02–1.03; P <0.001), previous coronary artery bypass graft (OR, 1.44; 95% confidence intervals, 1.17–1.77; P <0.001), left main (OR, 1.54; 95% confidence intervals, 1.21–1.96; P <0.001), use of rotational atherectomy (OR, 2.37; 95% confidence intervals, 1.80–3.11; P <0.001), and chronic total occlusions intervention (OR, 3.96; 95% confidence intervals, 3.28–4.78; P <0.001). Adjusted odds of adverse outcomes were higher in patients with CP for all major adverse coronary events, including stroke, bleeding, and mortality. Emergency surgery was required in 3% of cases. Predictors of mortality in patients with CP included age, diabetes mellitus, previous myocardial infarction, renal disease, ventilatory support, use of circulatory support, glycoprotein inhibitor use, and stent type. Conclusions—: Using a national PCI database for the first time, the incidence, predictors, and outcomes of CP were defined. Although CP as a complication of PCI occurred rarely, it was strongly associated with poor outcomes. Abstract : Supplemental Digital Content is available in the text.